2015
DOI: 10.1007/s40572-015-0061-0
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Food Animal Production and Community Health

Abstract: Industrial food animal production (IFAP) is a source of environmental microbial and chemical hazards. A growing body of literature suggests that populations living near these operations and manure-applied crop fields are at elevated risk for several health outcomes. We reviewed the literature published since 2000 and identified four health outcomes consistently and positively associated with living near IFAP: respiratory outcomes, methicillin-resistant Staphylococcus aureus (MRSA), Q fever, and stress/mood. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 118 publications
(174 reference statements)
1
62
0
Order By: Relevance
“…It is uncommon for other reviews to explicitly assess the risk of bias or to state explicit eligibility criteria. One review did discuss the limitations of the cross-sectional studies that included the use of prevalent outcomes [30]. The authors of that review concluded that “there was sufficient evidence of an association between living near IFAP (industrial food animal production) and respiratory outcomes, MRSA, Q fever, and stress/mood.” [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is uncommon for other reviews to explicitly assess the risk of bias or to state explicit eligibility criteria. One review did discuss the limitations of the cross-sectional studies that included the use of prevalent outcomes [30]. The authors of that review concluded that “there was sufficient evidence of an association between living near IFAP (industrial food animal production) and respiratory outcomes, MRSA, Q fever, and stress/mood.” [30].…”
Section: Discussionmentioning
confidence: 99%
“…One review did discuss the limitations of the cross-sectional studies that included the use of prevalent outcomes [30]. The authors of that review concluded that “there was sufficient evidence of an association between living near IFAP (industrial food animal production) and respiratory outcomes, MRSA, Q fever, and stress/mood.” [30]. The review authors also urged the use of prospective designs to obtain stronger evidence; this approach would provide a way to reduce the biases present in the current body of work.…”
Section: Discussionmentioning
confidence: 99%
“…Manure-borne E. coil and other fecal pathogens present a serious management challenge for large and small feedlot operations, as well as, for management of range-grazing herds of domesticated species (Bicudo and Goyal 2003; Gerber et al 2010; Hubbard et al 2004). There is a critical need to balance cost-effective and sustainable management options to allow for continued production along while adequately protecting human health from risk of food and waterborne disease outbreaks (Bicudo and Goyal 2003; Boxall et al 2009; Casey et al 2015; Gerber et al 2010). The implications of these public health risks in surface waters from animal operations have been well established since the mid-1970s (Hubbard et al 2004; Tian et al 2002), and various mitigation strategies (including vegetative filter strips) have been implemented since the 1980s to address removal of various runoff contaminants into public waters (Lim et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Potential routes of exposure for the public include contaminated milk or meat from livestock operations, crops from direct application of manure or manure-contaminated overland flow, and contamination into surface waters and drinking water (Bicudo and Goyal 2003). Increasing evidence illustrates a direct geographic correlation for increased risk for communities living in close proximity to food animal production areas or manure applied crop fields (Casey et al 2015). A major challenge for both large-scale production operations and small-scale local farming is how to ameliorate impacts of livestock on surface water quality to protect human health, while maintaining production and meeting nutritional needs (Hubbard et al 2004; Randolph et al 2007; Gerber et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A major challenge for both large-scale production operations and small-scale local farming is how to ameliorate impacts of livestock on surface water quality to protect human health, while maintaining production and meeting nutritional needs (Hubbard et al 2004; Randolph et al 2007; Gerber et al 2010). As faecal contamination of surface water bodies by livestock feed operations can be multi-factorial in nature, various management strategies must be employed to adequately reduce public health risk, including limits on proximity to surface water sources, duration and rotation of grazing time and various mitigation strategies to reduce the contribution of overland flow of manure-borne pathogens into surface waters (Doran and Linn 1979; Edwards et al 1997; Bicudo and Goyal 2003; Tyrell and Quinton 2003; Gerber et al 2010; Casey et al 2015). In recent years, vegetated filter strip (VFS) has emerged as a low-cost, locally implementable, best management practice option to minimize these health risk, particularly for small-scale operations or to reduce risk from open pasture-derived overland flow (Stout et al 2005; Liu et al 2008; McLaughlin et al 2013; Yu et al 2013).…”
Section: Introductionmentioning
confidence: 99%